Silver and gold nanoparticles characterization by SP-ICP-MS and AF4-FFF-MALS-UV-ICP-MS in human samples used for biomonitoring - Bocca, Beatrice; Battistini, Beatrice; Petrucci, Francesco (Talanta (Oxford), 2020)
The rapid increase in the use of silver (Ag) and gold (Au) nanoparticles (NPs) can be a potential risk to humans. Ag and Au NPs may enter the blood, accumulate in organs and be cleared from the body. It is therefore necessary to develop detection and quantification methods for Ag and Au NPs in human matrices. To this end, the inductively coupled plasma mass spectrometry was used as single particle detector (SP-ICP-MS) and coupled on-line with asymmetric flow field flow fractionation (AF4-FFF-ICP-MS), multi-angle scattering (MALS) and UV. Both methods enabled the qualitative and quantitative measurement of mixtures of Ag NPs (20, 60 and 100 nm) and Au NPs (5, 20, 40 and 60 nm) in human urine, blood and serum. Methods were validated by estimating linearity, limit of detection, resolution, repeatability, recovery and stability of Ag and Au NPs measurements in fluids. The SP-ICP-MS showed concentration limits for Ag and Au NPs lower than AF4-FFF-ICP-MS (pg/mL vs. ng/mL, respectively), while AF4-FFF-ICP-MS could detect smaller sized NPs (2–5 nm vs. 7–14 nm for SP-ICP-MS) with good resolution between monodispersed NPs fractions. In addition, MALS detector was more promising respect to higher sizes of Ag and Au NPs (>40 nm), while UV for lower sized particle (<20 nm). The observed performances will allow to use ICP-MS-based methods, also coupled to other detectors, to carry out human biomonitoring campaigns dedicated to the analysis of metallic NPs in the general population and in exposed subjects. [Display omitted] •Ag and Au nanoparticles (NPs) characterization in human urine, serum and blood.•Validation of SP-ICP-MS and FFF-MALS-UV-ICP-MS analysis.•Advantages and limitations of techniques.•Opportunity to perform human biomonitoring studies for metallic NPs.